Pengaruh Kualitas Layanan dan Citra Merek terhadap Kepuasan Pelanggan dan Niat Pembelian Sewa Kost di Singgahsini Mamikos - Anggetha, Dwi Asih; Albari, Albari (Penerbit Goodwood, 2024)
Purpose: This study explores the impact of service quality and brand image on customer satisfaction and rental purchase intention among Singgahini Mamikos users. Research Methodology: Convenience sampling was used to collect data from 200 Mamikos users who were looking for boarding houses in Jogja and Jakarta over the past six months. The analysis was conducted using Structural Equation Modelling (SEM) with AMOS to assess the relationships between variables. Results: The SEM analysis shows that service quality and brand image significantly and positively affect customer satisfaction and rental purchase intention. These results suggest that improving these factors can increase customer satisfaction and the likelihood of rental transactions. Limitations: This study's reliance on convenience sampling and focus on only two cities may limit the generalizability of the findings to broader populations or different geographic areas. Contribution: This study contributes to the understanding of how service quality and brand image drive customer satisfaction and purchase intention in the digital rental property market, thereby providing valuable insights for developing targeted business strategies.